Humoral and cellular immune responses in cattle upon Clostridium chauvoei vaccination and challenge - Rossi, Andrea; Guarnaschelli, Julio; Rial, Analía; Moreno, María; Rivera-Patron, Mariana; Iriarte, Andrés; Chabalgoity, José A. (Frontiers in Immunology, 2025)
IntroductionClostridium chauvoei is the causative agent of blackleg, a severe disease in cattle. Vaccination reduces disease incidence but the immune mechanisms that underlie vaccine-induced protection remain poorly understood, particularly the role of cellular immunity. In this study we characterized the humoral and cellular immune responses induced by a polyclostridial vaccine and assessed their correlation with protection against a C. chauvoei challenge.MethodsEleven six month old Hereford calves, seronegative for anti C. chauvoei antibodies, were randomized into vaccinated (n=8) and control (n=3) groups. Vaccinated animals received two doses of the vaccine at days 0 and 42-days. All animals were intramuscularly challenged with C. chauvoei spores (8,000 LD50) at day 69 post vaccination and monitored for clinical outcomes. Blood samples were collected at pre-vaccination and pre- and post-challenge. Humoral responses were quantified by specific in-house developed ELISA. Cytokine gene expression was measured in whole-blood (RT-qPCR for IFN γ, TNF α, TGF β1, IL 4, IL 17A, IL 12B, IL 10) upon antigenic stimulation. ResultsWhile vaccination protected cattle upon challenge and all animals survived, unvaccinated controls developed severe disease and died. Vaccination induced a strong specific antibody response although with inter-individual variation as well as a specific cytokine profile characterized by increased expression of IFN-γ, TGF-β1, and IL-4. Post-challenge, IFN-γ and IL-12B expression declined in vaccinated animals, but TGF-β1 persisted. High pre-challenge IgG, IFN-γ, and TGF-β1 were associated with protection, whereas increased IL-12B post-challenge was associated with disease severity. DiscussionThese findings demonstrate a coordinated interplay between humoral and cellular immune responses in vaccine-induced protection, with IFN-γ emerging as a potential biomarker in conjunction with antibody titre. The study provides a deeper further understanding on the immune mechanisms underlying vaccine-mediated protection against C. chauvoei and shall be relevant for the development of more effective vaccines.